The role of sex and ethnicity in the variability of estimated glomerular filtration rate ( eGFR ) in people with type 1 diabetes - Salma Ayis; Murat Ozdede; Luigi Gnudi; Thamer Alobaid; Panagiotis Pavlou; Anastasios Mangelis; Nikolaos Fountoulakis; Aicha Goubar; Janaka Karalliedde (Diabetic Medicine, 2026)
Abstract Aims To examine sex‐based differences in estimated glomerular filtration rate (eGFR) trajectories for people with type 1 diabetes (T1D) over 10 years and to test the hypothesis that sex and ethnicity interaction predicts eGFR decline. Methods A cohort of 1495 individuals, 48% men (81% White, 12% African‐Caribbean and 7% Other) and baseline eGFR ≥45 mL/min/1.73 m 2 was analysed. Group‐based trajectory modelling (GBTM) was used to identify eGFR sex‐specific trajectories, and linear mixed models were used to evaluate the role of sex and ethnicity interaction in predicting eGFR heterogeneity. Results Five eGFR trajectories were identified in both women and men. Rapid decline (>3 mL/min/1.73 m 2 /year) occurred in 5.75% of women and 10% of men. Among women, the group included 12.3% of the African‐Caribbean and 4.8% of the White; among men, it included 24.3% of the African‐Caribbean, 22.2% of the Asian and 8.3% of the White. Mild/Stable decline was observed in 16% of women and 27% of men. Mean eGFR was lower by (−20 [95% CI −25, −15] mL/min/1.73 m 2 /year) in African‐Caribbean women and (−15 [−21, −9]) in men, compared to White women and men respectively. The lowest eGFR sex gap observed in African‐Caribbeans, and the highest in ‘Other’. Conclusions Interactions between sex and ethnicity may determine the heterogeneity in kidney function decline.